The Impact of Work Flexibility, Work Environment, and Work-Life Balance on Employee Job Satisfaction at the Aceh Tamiang Inspectorate Office - Fachrurrazi, Muhammad; Wulandari, Sri Sukma; Mukhlis, Mukhlis; Syahputri, Indah Dwi; Shafwan, Shafwan; Safrida, Safrida (Economics, Business and Management Science Journal, 2025)
This study analyzes the influence of work flexibility, work environment, and work-life balance on employee job satisfaction at the Aceh Tamiang Inspectorate Office. Using a quantitative method with a survey approach, this study involved 48 respondents. Data was collected through questionnaires, which were then analyzed using multiple linear regression. The results showed that work flexibility, work environment, and work-life balance positively and significantly affected job satisfaction. Among the three variables, the work environment has the greatest influence with a regression coefficient of 0.45, followed by work flexibility (0.35) and work-life balance (0.30). Simultaneous tests showed that these three variables together affected job satisfaction with an F-count value of 15.72 and a p-value 0.001. The coefficient of determination (R²) of 0.65 shows that 65% of job satisfaction variability can be explained by these three variables. The conclusion of this study emphasizes the importance of work flexibility, a good work environment, and work-life balance to increase employee job satisfaction. The Aceh Tamiang Inspectorate Office is advised to strengthen policies related to these three factors to create a more supportive and productive work environment.